Clinical and biochemical assessment of the state of oral tissue in patients with paranoid schizophrenia of continuous flow - N. E. Dukhovskaya; S. V. Abramov; T. P. Vavilova; Yu. A. Mitronin; Yu. A. Ostrovskаyа; A. A. Dukhovskaya (LLC "Endo Press", 2019)
Research objective. To assess the state of oral tissue in patients with paranoid schizophrenia of continuous flow according to biochemical indices of mixed saliva and to compare with clinical parameters. Material and methods. 57 patients with continuous paranoid schizophrenia were divided into 5 groups according to age. The rate of salivation, pH was calculated, the activity of AST, ALT, APF, LDH, total protein, IL-1β, -4, -6, -10, TNF-α was determined in saliva. All the results obtained were processed by variational statistics, correlation analysis by Spearmen. Results and discussion. Patients with paranoid schizophrenia of the continuous course revealed an unfavorable clinical status of the oral tissues, which correlates with the parameters of mixed saliva.